PEMBERDAYAAN PERANAN ORANGTUA KEPADA ANAK-ANAK SEKOLAH MINGGU DALAM MENINGKATKAN NILAI PERSEMBAHAN DI GEREJA HKBP SIANTAR TIMUR TAHUN 2020/2021 - Nurliani Siregar; Sunggul Pasaribu; Esti Sirait (Nusantara Hasana Journal, 2021)
This research is "Empowering the role of parents for Sunday school children in increasing the value of offerings at the HKBP Resort Siantar Timur in 2020/2021". The role referred to in this case is the important task of parents in guiding, fostering children to increase awareness of children giving their offerings every Sunday at church. The relationship between father and mother must truly cultivate love in accordance with God's will for the child. In collecting the research data, a closed questionnaire (questionnaire) was used which was distributed and filled out by the respondents. Through this study, the authors hope to find out the extent to which the role of parents in empowering Sunday school children through empowerment in their respective families so that children, as the next generation can reach his goals and his life becomes the glory of God. The results of this study, the Church will increasingly equip parents in their service tasks. It is proven from the results of data X and data Y, each in the form of a normal distribution, using the formula: Chi squared (X2) table with a level of significance = 0.05, namely For data X (Role of parents) X2count = -166.27 while X2table = 9.49. And for data Y (Increasing awareness of children giving offerings) Y2count = -92.13 while Y2table = 9.49. Furthermore, the value of t-count = 4.58> ttable = 1.68, which means that there is a good relationship between the role of parents in raise awareness of children giving offerings.